Root Features Determine the Increasing Proportion of Forbs in Response to Degradation in Alpine Steppe, Tibetan Plateau - Zhang, Zhenchao; Sun, Jian (Frontiers in Environmental Science, 2020)
Understanding the response of plant community to degradation is fundamentally important for grassland conservation and management. The objective of this study is to examine the changes in soil properties and plant characteristics along a degradation gradient in alpine steppe, and explore the potential mechanisms that biotic and abiotic controls regulate plant community variations. We chose seven sequent degraded degrees, and conducted a field survey as well as soil and plant samplings in an alpine steppe in Northern Tibet. The results showed that soil water content (SWC), soil compaction (SCOM), soil total carbon (STC), and total nitrogen (STN) dramatically decreased along the degradation gradient. The species richness, overall aboveground biomass (AGB), and AGB of graminoids were apparently reduced with increasing degraded degrees, while AGB of forbs slightly increased. The increasing degradation levels induced a significant increase in the trade-off value of AGB of forbs, which was negatively associated with SWC, SCOM, STC, STN, and soil available nitrogen. The mean root length of forbs was significantly longer than that of graminoids (P<0.05). Moreover, the mean root diameter of the top 1/3 part of forbs was remarkably thicker than that of graminoids (P<0.05). These findings indicate that the degradation-induced cohesionless soils with insufficient water and nutrients together with the divergent root morphological traits of graminoids and forbs determine the plant community structure shift with grassland degradation. This study can improve the understanding of community succession of grassland degradation, and provide guidance for the management of degraded alpine steppe on the Tibetan Plateau.